Effects of a liquid cooling vest on physiological and perceptual responses while wearing stab-resistant body armor in a hot environment. Issue 2 (3rd April 2022) - Yuan, Mengqi; Wei, Yuchen; An, Qiqi; Yang, Jie
Abstract : This study determines the effects of a liquid cooling vest (LCV) on physiological and perceptual responses while wearing stab-resistant body armor (SRBA). Ten healthy male volunteers wearing SRBA performed human trials with the LCV and without (control) in a hot environment (30 °C and 40% relative humidity). Physiological parameters and perceptual responses were recorded during the tests. The results indicated that the difference in the mean skin temperature and scapula skin temperature between the two conditions was up to 1.2 and 2.5 °C, respectively. The LCV did not significantly decrease the core temperature, heart rate, sweat loss, oxygen consumption, rating of perceived exertion and restriction of movement. However, a significant difference was observed between conditions in terms of evaporation efficiency and thermal sensation. Therefore, the LCV attenuated an increase in thermal sensation but did not mitigate physiological strain. This work can provide fundamental knowledge for high-performance personal cooling system development.